Research on the Countermeasures of Building Smart Community Based on Cloud Computing (International Journal of Engineering and Computer Science, 2020)
Smart communities are the result of the evolution of communities under the development of new technologies. Many cities regard smart communities as one of the three regional demonstrations of smart city construction. Based on the experience of the construction of excellent intelligent communities at home and abroad, this paper analyzes the problems and difficulties in the current smart community construction, puts forward specific feasible countermeasures, and designs the smart community structure, which can promote the humanization of community governance, the integration of community services and the intelligentization of home life.